Application Server Architecture and BPEL promises and challenges. - Debnath, Amlan (SOA webservices journal.)
In recent years the application server has greatly evolved, expanding the set of core services provided by the infrastructure. The current Java platform supports XML data handling, scalability, load balancing and other capabilities that allow application level services to be developed more easily and deployed more reliably. This progression must now address developers' latest concerns regarding security, distributed transactions and reliable messaging because applications no longer stand alone-they're deployed into a technology ecosystem that can span departmental and organizational boundaries.